Edukasi Pencegahan Stunting melalui Penyuluhan dan Distribusi Leaflet di Kelurahan Sonraen Kabupaten Kupang - Lawalata, Patricia Yuniarti; Wea, Claudia Elda; Sius, Karolus Tatu; Indriyati, Indriyati; Kaha, Hendrikus Likusina (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Stunting is a serious nutritional problem and can have long-term impacts on children's growth and development. This program aims to increase public awareness of stunting prevention through counseling and distribution of brochures or leaflets in Sonraen Village, South Amarasi District, Kupang Regency. This activity includes providing information on the causes, impacts, and ways to prevent stunting, as well as distributing brochures containing educational materials that are easy to understand. The results of this activity show an increase in public knowledge about stunting and preventive measures. In addition, active community participation in discussions and questions and answers during counseling also increased. It is hoped that through ongoing education and effective dissemination of information, public awareness of the importance of stunting prevention can continue to be increased, so that it can reduce stunting rates in the Sonraen area. This program provides recommendations to continue the education program and expand the reach of information to other communities in Kupang Regency.